2021
DOI: 10.2147/jhc.s309570
|View full text |Cite
|
Sign up to set email alerts
|

Peritumoral Dilation Radiomics of Gadoxetate Disodium-Enhanced MRI Excellently Predicts Early Recurrence of Hepatocellular Carcinoma without Macrovascular Invasion After Hepatectomy

Abstract: Background: Whether peritumoral dilation radiomics can excellently predict early recrudescence (≤2 years) in hepatocellular carcinoma (HCC) remains unclear. Methods: Between March 2012 and June 2018, 323 pathologically confirmed HCC patients without macrovascular invasion, who underwent liver resection and preoperative gadoxetate disodium (Gd-EOB-DTPA) MRI, were consecutively recruited into this study. Multivariate logistic regression identified independent clinicoradiologic predictors of 2-year recrudescence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 62 publications
5
35
1
Order By: Relevance
“…Conjoined uAI Research Portal software (United Imaging Intelligence, China) that was embedded into the widely used package-PyRadiomics (https://pyradiomics.readthedocs.io/en/ latest/index.html) was used for radiomics analysis on the region of interest (ROI) of the subject's primary tumor. The workflow of radiomics mainly included the following steps: lesion segmentation, feature extraction, feature selection, and machine learning modeling (12)(13)(14)(15).…”
Section: Radiomics Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjoined uAI Research Portal software (United Imaging Intelligence, China) that was embedded into the widely used package-PyRadiomics (https://pyradiomics.readthedocs.io/en/ latest/index.html) was used for radiomics analysis on the region of interest (ROI) of the subject's primary tumor. The workflow of radiomics mainly included the following steps: lesion segmentation, feature extraction, feature selection, and machine learning modeling (12)(13)(14)(15).…”
Section: Radiomics Data Processingmentioning
confidence: 99%
“…The patients were randomly assigned into a training set (70%) and a test set (30%) (12,16,17). We used two feature selection methods, mRMR and LASSO, to select the features.…”
Section: Feature Selectionmentioning
confidence: 99%
“…Improving the ability to preoperatively identify these high-risk patients will guide surgical management, postoperative monitoring, and treatment intervention (127,128). The radiomic model based on preoperative MRI can be used as a new tool to predict early relapse (18,19,(129)(130)(131)(132)(133)(134), relapsefree survival (135) and overall survival (OS) (136,137)…”
Section: Prediction Of Relapse and Prognosis After Surgical Resectionmentioning
confidence: 99%
“…Radiomics, a new technology, can transform the potential histopathological and physiological information in images into high-dimensional quantitative image features that can be mined (6,7).The study of radiomics will contribute to the early diagnosis and treatment of HCC and ultimately improve survival (8,9). In recent years, many studies have confirmed the application values of magnetic resonance imaging (MRI) radiomics in the diagnosis and differentiation (10,11), histological grading (12,13), microvascular invasion (MVI) assessment (14,15), radiogenomics (16,17),prediction of relapse and prognosis after surgical resection (18)(19)(20), response to transarterial chemoembolization(TACE) (21,22) and systemic treatment efficacy of HCC (23).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that tumor diameter greater than 5 cm was closely related to ER and high mortality ( 22 24 ). However, few studies specifically predict ER of solitary HCC with a diameter ≤ 5 cm after hepatectomy.…”
Section: Introductionmentioning
confidence: 99%